2007
DOI: 10.1093/nar/gkm658
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the rRNA decoding site of eukaryotic cytosolic ribosomes in bacteria

Abstract: Structural and genetic studies on prokaryotic ribosomes have provided important insights into fundamental aspects of protein synthesis and translational control and its interaction with ribosomal drugs. Comparable mechanistic studies in eukaryotes are mainly hampered by the absence of both high-resolution crystal structures and efficient genetic models. To study the interaction of aminoglycoside antibiotics with selected eukaryotic ribosomes, we replaced the bacterial drug binding site in 16S rRNA with its euk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 41 publications
2
115
0
Order By: Relevance
“…Thus, A1408 and G1491 facilitate the proper insertion of ring I carrying either an amino or hydroxyl group into the binding site, whereas G1408 and A1491 cause the binding pocket to be shallower and less stable, thus preventing proper insertion and binding of ring I (Recht et al 1999b;Lynch and Puglisi 2001a;Westhof, 2001, 2003). Consistent with these findings, a recent study demonstrated that the introduction of the eukaryotic decoding site into bacteria 16S rRNA conferred aminoglycoside resistance comparable to eukaryotic ribosomes (Hobbie et al 2007).…”
Section: Discussionmentioning
confidence: 54%
“…Thus, A1408 and G1491 facilitate the proper insertion of ring I carrying either an amino or hydroxyl group into the binding site, whereas G1408 and A1491 cause the binding pocket to be shallower and less stable, thus preventing proper insertion and binding of ring I (Recht et al 1999b;Lynch and Puglisi 2001a;Westhof, 2001, 2003). Consistent with these findings, a recent study demonstrated that the introduction of the eukaryotic decoding site into bacteria 16S rRNA conferred aminoglycoside resistance comparable to eukaryotic ribosomes (Hobbie et al 2007).…”
Section: Discussionmentioning
confidence: 54%
“…Ribosome concentrations of 70S were determined by absorption measurements on the basis of 23 pmol ribosomes per A 260 unit. Integrity and functional activity of purified 70S ribosomes was determined by analytical ultracentrifugation and by assessing their capacity to form initiation complexes, as described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…A reaction mixture containing M. smegmatis tRNA bulk , amino acids, S100 extract, energy mix, pyruvate kinase, and polyamines was preincubated with 30 M [ 14 Cell-Free Luciferase Translation Assays. Purified 70S hybrid ribosomes were used in a coupled transcription-translation reaction as described previously (29). The reaction mixture was incubated for 60 min at 37°C, stopped on ice, and luciferase assay substrate (Promega) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Ribosomes were isolated from bacterial cell pellets as described (36). For further fractionation, isolated ribosomes were resuspended in overlay buffer [20 mM Tris⅐HCl (pH 7.4), 60 mM NH4Cl, 5.25 mM MgCl2, 0.25 mM EDTA, 3 mM 2-mercaptoethanol, and 5% sucrose] loaded on a sucrose gradient (10 -40% sucrose in overlay buffer) and centrifuged in a Beckman Ti 15 rotor at 28,000 rpm for 18 h. Gradient fractions were collected by unloading the zonal rotor with 50% sucrose in overlay buffer.…”
Section: Methodsmentioning
confidence: 99%
“…70S ribosome concentrations were determined by absorption measurements on the basis of 23 pmol per A 260 unit. Integrity and functional activity of purified 70S ribosomes was determined by analytical ultracentrifugation and by assessing their capacity to form initiation complexes, as described (36).…”
Section: Methodsmentioning
confidence: 99%